The host : a novel - Meyer, Stephenie, 1973- (New York : Little, Brown, 2008)
Melanie, whose mind has been almost completely taken over by an alien named Wanderer, convinces the alien to search for her lost lover, who fled the extraterrestrial invasion, and tries to find a way in which she and Wanderer can coexist.
Library Journal Starred.
School Library Journal.
Wilson's Fiction.
Booklist, March 2008.
Library Journal Starred, April 2008.
Publisher's Weekly, March 2008.
Keywords: Spirit possession -- Fiction; Love stories; Science fiction; Spirits -- Fiction; Love stories; Science fiction